Kapingamarangi Lexicon - Lieber, Michael D.; Dikepa, Kalio H. (University of Hawai'i Press, 2023)
The Kapingamarangi lexicon is designed for use by the Kapinga in their own classrooms as a teaching resource, by comparative linguists interested in Polynesian languages, and as an aid for those learning Kapinga. The lexicon presents an exhaustive list of 6,000 root words and their use in deriving words, compounds, and phrases. An introduction delineates the rules of word structure in the Kapinga language in simple, nontechnical English with explanatory footnotes in Kapinga. In addition, the introduction includes material directed primarily to linguists dealing with such problems as word classes, problems of reduplication, and the like. The lexicon itself is arranged in three listings: Kapingamarangi-English, English-Kapingamarangi, and by root words, demonstrating how they are systematically derived and compounded.